Taming the escalating costs of Ireland’s community drugs schemes - Fortescue-Webb, Duncan (Trinity Student Medical Journal, 2010)
A reduced public budget has increased pressure to improve the efficiency of healthcare provision in Ireland. Legislative changes to reduce margins throughout the drugs supply chain and increase patient co-payments have recently been implemented. The background and implications of these changes are considered for manufacturers, wholesalers, pharmacists, patients and the public purse. Together, the changes are predicted to reduce the cost of providing drugs in the community in 2010 by nearly €270 million (11% of the projected €2.4 billion they would otherwise cost). However, underlying growth trends in drugs expenditure, particularly in the burgeoning high-tech drugs market, mean that although recent changes should contain the cost of drugs in 2010 at a level similar to 2009, annual growth of 12% is likely to resume thereafter unless additional reform is implemented. Slated future legislative changes that could be worth a further €200 million or more annually include: reference pricing, pharmacist-led substitution, renegotiation of manufacturer prices, and disinvestment of non-cost-effective drugs from public schemes. Finally, ways to improve prescriber habits are considered that could save an additional €100 million annually. These include periodic and critical reviews of patient prescriptions, more judicious use of antibiotics, generic prescribing, prescriber awareness of drug prices, and provision of prescribing software.